Experiences of Sexual Harassment among Nurses in a Tertiary Hospital - Pandey, Apsara; Rai, Lalita; Acharya, Devaka Kumari; Dangol, Bhuwan Kumari (Journal of Advanced Academic Research, 2022)
Introduction: Sexual harassment among nurses is a major issue of work place, health and safety that seriously affects patient care. It is more common among nurses. The aim of this study was to identify experiences of sexual harassment among nurses in a tertiary hospital. Method: A descriptive cross-sectional design was used to find out the experience of sexual harassment among nurses. Two hundred and twenty-three, nurses working in a tertiary hospital were selected using purposive sampling technique. Data were collected through structured, self-administered questionnaire. Ethical approval was obtained from Institutional Review Committee Institute of Medicine Kathmandu. Data were analyzed using Statistical Package for Social Science (version 16) Results: The mean age of the nurses was 29.6 (SD ± 7.4) years and 57.0% were married. Most of the nurses (85.2%) performed as roster basis in all shifts (rotation; morning, evening and night) duty and 15.2% of the nurses were from emergency ward. Median duration of work experience was 4.17 years (range= 6months to 31 years). Total 18.5% nurses had experienced some kinds of sexual harassment in their workplace. More than half (53.8%) each were harassed by doctors and visitors; 46.2% of the nurses were harassed in emergency/ general ward/ operation theatre; 30.8% were harassed at bed side; 38.5% were harassed in the evening shift and 66.7% were harassed when they are working alone. Likewise, 28.2% reported the incident of sexual harassment; 90.9% reported verbally and 89.7% suggested that hospital need to develop policy against sexual harassment. Nurses with night shift duty (100.0%), PCL/ B. Sc level of education (20.0%), unmarried (21.8%), staff nurse (201.7%), slim body (21.3%), fierce nature (33.3%) and beautiful looks (29.8%) were more frequently victimized but that was not statistically significant. Conclusions: Workplace sexual harassment is frequent among nurses working at tertiary hospital. However, reporting rate is very low due to fear of negative consequences and lack of knowledge about how and where to report. Proper policy, law and reporting mechanism should be developed to combat sexual harassment among nurses.